Assessment of tidal and anthropogenic impacts on coastal waters by exploratory data analysis: an example from Port Dickson, Strait of Malacca, Malaysia - Praveena, Sarva Mangala; Siraj, Siti Shapor; Aris, Ahmad Zaharin; Al-Bakri, Noraidi Mustafa; Suleiman, Ahmad Kimon; Zainal, Ahmad Anuar (Taylor & Francis, 2013)
Tidal variations in coastal waters have been often related to nutrients. However, few attempts have been made to investigate the difference in conditions between high and low tides and predict the responses in coastal waters related to nutrients and physicochemical properties. This study covered an area of 18 km from north Tanjung Gemuk to south Tanjung Tuan in Port Dickson, facing the Strait of Malacca, one of the busiest shipping routes in the world. This research investigated the relation between tides, nutrients, and physicochemical properties of water in order to provide the basis to describe the effects of tides in the coastal waters of Port Dickson, a central attraction of the Strait of Malacca. Relatively all of the studied parameters (physicochemical properties and nutrients concentration) showed higher values at low tide than at high tide, except for salinity and electrical conductivity. Relationships between nutrients and physicochemical properties at high and low tides were studied using Spearman correlation analysis. It may be noted that the relationship between nutrients and physicochemical properties at high and low tides varies from weak (r = 0.400) to moderate (r = 0.558). The multivariate statistical technique principal components analysis (PCA) was employed to better interpret information about the interaction between nutrients and physicochemical properties at high and low tides. The current study determined that there is an anthropogenic impact at increased levels of nutrient concentration, primarily for ammonia and phosphate. This study has provided new updated baseline data for the coastal waters of Port Dickson related physicochemical properties and nutrient concentration. The new updated baseline data will be used to identify and prioritize future studies and regulatory plans in Port Dickson as well as the Strait of Malacca. This data is also relevant to forensic investigations of potential future pollution events in the area.